2007
DOI: 10.1186/1546-0096-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and lipid profile in children with Juvenile Idiopathic Arthritis

Abstract: JIA patients do not present significant increased concentration of Hcy despite the use of MTX, probably due to the folate supplementation. The mild abnormalities in the lipidogram may reflect a current concern with diet and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…Dyslipidemia with decreased HDL-C levels and elevated levels of low-density lipoprotein cholesterol, triglycerides, and total cholesterol were identified with polyarticular juvenile idiopathic arthritis by Marangoni et al [22]: however, they presented that dyslipidemia with decreased HDL-C was not affected by disease activity or therapy. Another two studies showed an insignificant diminution of LDL-C in patients with active disease when compared to either patients without active disease or to controls [23], [24]. However, the results could be biased due to factors that were not the controlled and the lack of longitudinal study design.…”
Section: Discussionmentioning
confidence: 98%
“…Dyslipidemia with decreased HDL-C levels and elevated levels of low-density lipoprotein cholesterol, triglycerides, and total cholesterol were identified with polyarticular juvenile idiopathic arthritis by Marangoni et al [22]: however, they presented that dyslipidemia with decreased HDL-C was not affected by disease activity or therapy. Another two studies showed an insignificant diminution of LDL-C in patients with active disease when compared to either patients without active disease or to controls [23], [24]. However, the results could be biased due to factors that were not the controlled and the lack of longitudinal study design.…”
Section: Discussionmentioning
confidence: 98%
“…Um estudo feito com 51 crianças com AIJ (idade média de 11 anos) por Gonçalves et al 14 também encontrou diminuição de HDL, mas, ao contrário do presente estudo, esses autores verifi caram também um aumento de TG. Em nosso estudo, a pre- Na presente análise, observou-se também uma tendência para pacientes com o subtipo oligoarticular demonstrarem aumento do LDL.…”
Section: Discussionunclassified
“…Dies zeigte sich insbesondere bei Patienten mit systemischer JIA und bei Patienten mit hoher Krankheitsaktivität. Im Gegensatz dazu fanden Goncalves et al [60] bei Kindern mit JIA niedrigere VLDL-und Triglycerid-Werte als bei gesunden Kontrollen. Eine weitere Studie zeigte mit Ausnahme einer Reduktion des LDL-Cholesterins (Low Density Lipoprotein) keine signifikanten Anomalien des Lipidprofils bei Heranwachsenden mit JIA [61].…”
Section: Dyslipidämieunclassified